1993
DOI: 10.1111/j.1471-0528.1993.tb14267.x
|View full text |Cite
|
Sign up to set email alerts
|

Denervation and re‐innervation of the urethral sphincter in the aetiology of genuine stress incontinence: an electromyographic study

Abstract: Objective To investigate the role of altered innervation of the urethral sphincter in the genesis of genuine Design Prospective observational study.Setting Tertiary referral centre urodynamics unit.Subjects Sixty-eight women, 33 with urodynamically proven pure genuine stress incontinence and 35Interventions Concentric needle electrornyography of the urethral striated sphincter. Main outcome measuresThe means of motor unit potential duration, number of changes in polarity and the amplitude of individual motor u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Delayed conduction time to the striated urethral sphincter or increased single ¢ber density has been observed after delivery [Krieger et al, 1988;Allen et al, 1990] and associated with stress incontinence Krieger et al, 1988;Smith et al, 1989a]. In contrast, Barnick and Cardozo [1993a] found abnormal concentric needle electromyography equally commonly in women with genuine stress incontinence as in an age-and parity-matched group without a history of stress incontinence. Surprisingly, women with a degenerated and consequently a regenerated urethral sphincter had a higher urethral closure pressure [Barnick and Cardozo, 1993b].…”
Section: E¡erent Somatic Nerve Functionmentioning
confidence: 83%
“…Delayed conduction time to the striated urethral sphincter or increased single ¢ber density has been observed after delivery [Krieger et al, 1988;Allen et al, 1990] and associated with stress incontinence Krieger et al, 1988;Smith et al, 1989a]. In contrast, Barnick and Cardozo [1993a] found abnormal concentric needle electromyography equally commonly in women with genuine stress incontinence as in an age-and parity-matched group without a history of stress incontinence. Surprisingly, women with a degenerated and consequently a regenerated urethral sphincter had a higher urethral closure pressure [Barnick and Cardozo, 1993b].…”
Section: E¡erent Somatic Nerve Functionmentioning
confidence: 83%
“…There are no available data in the literature as far as we know assessing any possible relation between PNTML and different stages of prolapse. Other investigators, using concentric needle electrode electromyography, found no statistically significant changes in motor unit potential duration of muscle fibers of the striated urethral sphincter and suggested that denervation of the striated urethral sphincter is not a major etiological factor in the development of GSI [15]. Use of quantitative electromyographic analysis and single-fiber measurements are indicative of peripheral nerve damage in women with GSI [16].…”
Section: Discussionmentioning
confidence: 99%
“…Fall et al [1989] provided similar evidence of underlying neurological disease in patients with overactive bladder, by utilizing the ice-water test of urothelial hypersensitivity, and Wyndaele [1993], testing electrosensitivity in the lower urinary tract, revealed abnormal innervation in 29% of patients with no previous evidence of neuropathy. Several studies have described electrophysiological evidence of pudendal nerve damage in stress urinary incontinent women, presumably related to obstetric injury [Anderson, 1984;Snooks et al, , 1985Barnick and Cardozo, 1993;Aanestad and Flink, 1999;Weidner et al, 2000]. Fidas et al [1988] used electrophysiological and radiological approaches to reveal neurogenic defects in every other case of female genuine stress incontinence, while Hale et al [1999], focusing on the striated urethral sphincter, presented both electrophysiological and histological evidence of a neurogenic contribution to genuine stress incontinence.…”
Section: Neurogenic Lutdmentioning
confidence: 97%